Management of antithrombotic agents in dermatologic surgery before and after publication of the corresponding German evidence‐based guideline. (14th March 2018) - Gaskins, Matthew; Dittmann, Martin; Eisert, Lisa; Werner, Ricardo Niklas; Dressler, Corinna; Löser, Christoph; Nast, Alexander
Summary: Background: A survey in 2012 revealed marked heterogeneity in the management of antithrombotic agents in dermatologic surgery in Germany. An evidence‐based guideline on this topic was published for the first time in 2014. Methods: Using the same study sample, we conducted an anonymous survey on the management of antithrombotic agents and familiarity with the guideline. We reported the results as relative frequencies and compared them with those from 2012. Results: We analyzed a total of 208 questionnaires (response rate: 36.6 %). A large majority of dermatologists reported performing minor procedures without discontinuing low‐dose aspirin (≤ 100 mg), clopidogrel, or direct oral anticoagulants. In contrast, antithrombotic management was still heterogeneous in the context of major procedures, especially among office‐based dermatologists. Overall, there was an increase in the proportion of dermatologists who managed phenprocoumon, aspirin, and clopidogrel in compliance with the guideline. For example, while 53.8 % of hospital‐based dermatologists and 36.3 % of office‐based dermatologists had performed large excisions on continued low‐dose aspirin treatment in 2012, these figures showed an increase to 90.2 % and 57.8 %, respectively, by 2017 (phenprocoumon: from 33.8 % and 11.9 % to 63.9 % and 29.9 %, respectively; clopidogrel: from 36.9 % and 23.2 % to 63.9 % and 30.6 %, respectively). Among hospital dermatologists a large proportion was familiar with the guideline and considered it to be useful. Conclusions: Our results suggest that compliance with the German guideline on the perioperative management of antithrombotics in dermatologic surgery has increased for all procedures. Despite this positive development, greater efforts are needed to improve implementation of the guideline and address barriers to its use in everyday practice.